Hematopoietic stem cell transplantation is effective in achieving long-term survival for post-aplastic anemia myeloid neoplasms: the EBMT Severe Aplastic Anemia Report - Pedro Henrique Prata; Dirk-Jan Eikema; Brian Piepenbroek; Austin Kulasekararaj; Beatrice Drexler; Jennifer M-L. Tjon; Krista Vaht; Mahmoud Aljurf; Patrice Chevallier; Tobias Gedde-Dahl; Ain Kaare; Urpu Salmenniemi; et al. (Haematologica, 2025)
Aplastic anemia (AA) transformation into myelodysplastic syndromes (MDS) or acute myeloid leukemia (AML) is associated with a dismal prognosis. Hematopoietic stem cell transplant offers the sole possibility of cure, but data on long-term survival are scarce. We retrospectively analyzed 270 patients transplanted for MDS, AML, or an isolated cytogenetic abnormality after a diagnosis of AA or paroxysmal nocturnal hemoglobinuria reported to the EBMT. The median age at transplantation was 39 years. The 5-year overall survival (OS) rate was 64%, unaffected by chromosome 7 abnormalities, age at transplant, sex, interval from clonal evolution to transplant, and intensity of conditioning regimen. The 5-year non-relapse mortality rates were 34% (95% CI, 25-42%) for MDS patients and 19% (95% CI, 7-31%) for AML patients and were higher following a myeloablative conditioning regimen. The five-year relapse rate was 12% (95% CI, 6-19%) for MDS and 22% (95% CI, 9-35%) for AML. Our study’s survival estimates reflect a younger cohort of patients, considering the bimodal distribution of aplastic anemia. Conditioning regimen intensity did not affect relapse. For MDS patients, pretreating before transplant did not improve survival nor reduce relapse. Transplantation is feasible and effective in achieving long-term survival for transplant-eligible post-AA myeloid neoplasm patients. MDS patients may benefit from upfront RIC transplant, limiting toxicity without higher relapse. Posttransplant maintenance therapies to reduce the relapse incidence among AML patients might be warranted.